Faradaic Pixels for Precise Hydrogen Peroxide Delivery to Control M‐Type Voltage‐Gated Potassium Channels. Issue 3 (26th November 2021) - Abdullaeva, Oliya S.; Sahalianov, Ihor; Silverå Ejneby, Malin; Jakešová, Marie; Zozoulenko, Igor; Liin, Sara I.; Głowacki, Eric Daniel
Abstract: H2 O2 plays a significant role in a range of physiological processes where it performs vital tasks in redox signaling. The sensitivity of many biological pathways to H2 O2 opens up a unique direction in the development of bioelectronics devices to control levels of reactive‐oxygen species (ROS). Here a microfabricated ROS modulation device that relies on controlled faradaic reactions is presented. A concentric pixel arrangement of a peroxide‐evolving cathode surrounded by an anode ring which decomposes the peroxide, resulting in localized peroxide delivery is reported. The conducting polymer (poly(3, 4‐ethylenedioxythiophene) (PEDOT), is exploited as the cathode. PEDOT selectively catalyzes the oxygen reduction reaction resulting in the production of hydrogen peroxide (H2 O2 ). Using electrochemical and optical assays, combined with modeling, the performance of the devices is benchmarked. The concentric pixels generate tunable gradients of peroxide and oxygen concentrations. The faradaic devices are prototyped by modulating human H2 O2 ‐sensitive Kv7.2/7.3 (M‐type) channels expressed in a single‐cell model ( Xenopus laevis oocytes). The Kv7 ion channel family is responsible for regulating neuronal excitability in the heart, brain, and smooth muscles, making it an ideal platform for faradaic ROS stimulation. The results demonstrate the potential of PEDOT to act as an H2 O2 delivery system, paving the way to ROS‐based organic bioelectronics. Abstract : Microfabricated electrochemical devices that precisely control oxygen and hydrogen peroxide gradients for biological experiments are presented.